Comprehensive analysis of 5‐hydroxymethylcytosine in zw10 kinetochore protein as a promising biomarker for screening and diagnosis of early colorectal cancer. Issue 3 (6th July 2020) - Dang, Yanqi; Hu, Dan; Xu, Jingjuan; Li, Chunlin; Tang, Yingjue; Yang, Zhenhua; Liu, Yang; Zhou, Wenjun; Zhang, Li; Xu, Hanchen; Xu, Yangxian; Ji, Guang
Abstract: Background: As a new epigenetic biomarker, 5‐hydroxymethylcytosine (5hmC) is broadly involved in various diseases including cancers. However, the function and diagnostic performance of 5hmC in colorectal cancer (CRC) remain unclear. Results: High‐throughput sequencing was used to profile 5hmC levels in adjacent normal colon, advanced adenomas, and CRC. The expression and 5hmC levels in zw10 kinetochore protein (ZW10) were significantly increased in the tissues and blood samples for patients with advanced adenoma and CRC, and were much higher in the early stages of CRC (I and II). The receiver operating characteristic analysis had potential diagnostic value for CRC. The area under the curve (AUC) of ZW10 5hmC levels in tissue samples of CRC was 0.901. In blood samples, the AUC was 0.748 for CRC. In addition, the ZW10 5hmC level had much higher diagnostic performance in early stages of CRC (AUC = 0.857) than it did in advanced stages (AUC = 0.594). Compared with FHC cell, ZW10 expression in HT29 cell was significantly increased. The ZW10 knockdown could inhibit cell proliferation and the ZW10 overexpression could promote cell proliferation in HT‐29 cell. Furthermore, ZW10 knockdown inhibited AKT and mTOR phosphorylation, and ZW10 overexpression promoted AKT and mTOR phosphorylation. Conclusions: The ZW10 5hmC level may serve as an effective epigenetic biomarker for minimally invasive screening and diagnosis of CRC, and it has higher diagnostic performance in early stages of CRC than it does in advanced stages. In addition, ZW10 could regulate CRC progression through the AKT‐mTOR signaling.